Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1097/ta.0b013e3182127840
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the Saline Load Test in Diagnosis of Traumatic Elbow Arthrotomies

Abstract: Our results demonstrate that 40 mL of fluid must be injected to identify the majority of traumatic arthrotomies about the elbow. Moreover, adding range of motion after the injection increases the detection rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 13 publications
1
25
0
Order By: Relevance
“…This finding is contradictory to reported results for the knee, elbow, and ankle, where saline load volume showed no such correlation. 2,3,5,6 However, Bariteau et al did find saline volumes required for extravasation in the ankle to be 14.5 mL in males and 7.3 mL in females with a p-value of 0.071. Crisco et al analyzed CT reconstructions to show that carpal bones are significantly larger in males.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…This finding is contradictory to reported results for the knee, elbow, and ankle, where saline load volume showed no such correlation. 2,3,5,6 However, Bariteau et al did find saline volumes required for extravasation in the ankle to be 14.5 mL in males and 7.3 mL in females with a p-value of 0.071. Crisco et al analyzed CT reconstructions to show that carpal bones are significantly larger in males.…”
Section: Discussionmentioning
confidence: 98%
“…Open wrist injuries have the potential to cause significant morbidity if not identified and treated urgently. 1 The saline load test for open arthrotomy, while well studied in various joints, [2][3][4][5][6] has not been studied in the wrist. In our study, we utilized wrist arthroscopy to simulate an arthrotomy and characterize the saline load test within the wrist.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 ). Six of these studies reported data from the SLT of the adult knee 4 , 5 , 7 , 8 , 10 , 11 one study reported data from SLT of the pediatric knee, 12 one study reported data from the wrist, 13 one study reported on data from cadaveric elbows, 14 and one study reported data from several different joints. 15 Additional cross-referencing of these studies yielded no further studies.…”
Section: Methodsmentioning
confidence: 99%
“…Saline Solution Load Test to Identify Traumatic Arthrotomy of the Elbow ¤ A posterior arthrotomy was created in thirty-six cadaveric elbows, and a load test using 20 mL of saline solution was performed [11][12][13] . If the saline solution load test with range of motion was negative, the injection was continued until extravasation of fluid was achieved.…”
Section: Functional Elbow Motion Redefinedmentioning
confidence: 99%